Reflective practice of nurse residents in the teaching-learning process in teaching hospitals - Ana Carolina de Oliveira Paiva; Kênia Lara Silva (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To analyze reflective practice in the teaching-learning process of nurses in residency programs in teaching hospitals in Minas Gerais, Brazil. Methods: Case study, based on the reflective practice framework, conducted in two teaching hospitals. Observation and interviews were conducted with first and second-year residents, and five participants were included for in-depth analysis, with their data subjected to frequency distribution analysis and Critical Discourse Analysis. Results: In 519 observed activities, elements of reflection were identified in 22.2%, especially active listening and expression of doubts. Discourses indicated practice as the best moment for teaching-learning due to its potential to generate reflections. Learning by doing and case discussion were considered potential strategies for reflective learning. Conclusion: Know-in-action reflection was evidenced as the predominant formative aspect for residents, with few opportunities for reflection on reflection-in-action.